Digital Malaysia development and challenges - Mohamed, Shafizan (2019)
The digitalisation process of the Malaysian media had its root in Dr. Mahathir's grand plan to make Malaysia a developed country by the year 2020. This presentation charters the development of the digitisation of the Malaysian media from the establishment of MSC to the current move towards adopting 5G technologies. The presentation also discusses about the challenges Malaysia face in it's digitisation journey.